2010
DOI: 10.1002/adsc.200900826
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Long Syntheses Short: Access to Non‐Natural Tyrosine Derivatives Employing an Engineered Tyrosine Phenol Lyase

Abstract: Abstract:The chemical synthesis of 3-substituted tyrosine derivatives requires a minimum of four steps to access optically enriched material starting from commercial precursors. Attempting to short-cut the cumbersome chemical synthesis of 3-substituted tyrosine derivatives, a single step biocatalytic approach was identified employing the tyrosine phenol lyase from Citrobacter freundii. The enzyme catalyses the hydrolysis of tyrosine to phenol, pyruvate and ammonium as well as the reverse reaction, thus the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…To identify the position of methylation, the methylated l ‐DOPA product from a 10 mL overnight Pcm10 reaction was purified and subjected to 1 H NMR analysis (Figure S3). The 1 H shifts are consistent with those reported for 4‐methyl‐ l ‐DOPA, but differ from those of 3‐methyl‐ l ‐DOPA . This result indicated that Pcm10 methylates l ‐DOPA at the 4‐hydroxy position, consistent with the structure of pepticinnamin E. No methyltransfer activity was observed when Pcm10 was incubated with l ‐tyrosine, thus suggesting that hydroxylation of l ‐tyrosine occurs prior to 4‐methylation.…”
Section: Methodssupporting
confidence: 78%
“…To identify the position of methylation, the methylated l ‐DOPA product from a 10 mL overnight Pcm10 reaction was purified and subjected to 1 H NMR analysis (Figure S3). The 1 H shifts are consistent with those reported for 4‐methyl‐ l ‐DOPA, but differ from those of 3‐methyl‐ l ‐DOPA . This result indicated that Pcm10 methylates l ‐DOPA at the 4‐hydroxy position, consistent with the structure of pepticinnamin E. No methyltransfer activity was observed when Pcm10 was incubated with l ‐tyrosine, thus suggesting that hydroxylation of l ‐tyrosine occurs prior to 4‐methylation.…”
Section: Methodssupporting
confidence: 78%
“…To efficiently introduce amino groups to convert phenols, pyruvate, and ammonia into ( S )‐α‐amino acids (Figure b), we chose the variant M379V of the recombinant TPL from Citrobacter freundii ( Cf TPL M379V ) because of its broad substrate scope (Seisser et al, ). The gene of Cf TPL M379V was cloned in plasmid pET28a and expressed in E. coli BL21, designated as E. coli 01 (0.086 U/mg cells, and 0.039 mg TPL proteins/mg cells; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…They are of great importance in the fields of fine chemicals synthesis, cosmetics, and pharmaceutical manufacturing (Busto et al, ; Busto, Simon, Richter, & Kroutil, ; Hou et al, ; Lütke‐Eversloh, Santos, & Stephanopoulos, ; Xue, Cao, & Zheng, ). For example, tyrosine derivatives play prominent roles in the synthesis of pharmaceuticals (Dennig, Busto, Kroutil, & Faber, ; Seisser et al, ). Among them, ʟ‐tyrosine is used as a dietary supplement and an important precursor of thyroxine, adrenaline, and 3,4‐dihydroxy‐ʟ‐phenylalanine (ʟ‐DOPA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme was applied in the reverse direction for the synthesis of tyrosine derivatives 144 . The variant M379V was the most active mutein for the preparation of 3′‐substituted tyrosines derived from ortho ‐substituted phenols (Scheme ) 216…”
Section: Miscellaneousmentioning
confidence: 99%